ESTIMATION OF VIBRATION INFLUENCE ON THE WORKERS IN FOUNDRY - A. M. Lazarenkov; S. A. Horeva; V. V. Melnichenko (Литьë и металлургия)
Estimation of the noise influence on the workers in foundry is given. The results of investigations of noise levels of used foundry equipment are given.